Critical Role of Flanking Residues in NGR-to-isoDGR Transition and CD13/Integrin Receptor Switching - Curnis, Flavio (American Society for Biochemistry and Molecular Biology, 2010)
Various NGR-containing peptides have been exploited for targeted delivery of drugs to CD13-positive tumor neovasculature. Recent studies have shown that compounds containing this motif can rapidly deamidate and generate isoaspartate-glycine-arginine (isoDGR), a ligand of αvβ3-integrin that can be also exploited for drug delivery to tumors. We have investigated the role of NGR and isoDGR peptide scaffolds on their biochemical and biological properties. Peptides containing the cyclic CNGRC sequence could bind CD13-positive endothelial cells more efficiently than those containing linear GNGRG. Peptide degradation studies showed that cyclic peptides mostly undergo NGR-to-isoDGR transition and CD13/integrin switching, whereas linear peptides mainly undergo degradation reactions involving the α-amino group, which generate non-functional six/seven-membered ring compounds, unable to bind αvβ3, and small amount of isoDGR. Structure-activity studies showed that cyclic isoDGR could bind αvβ3 with an affinity >100-fold higher than that of linear isoDGR and inhibited endothelial cell adhesion and tumor growth more efficiently. Cyclic isoDGR could also bind other integrins (αvβ5, αvβ6, αvβ8, and α5β1), although with 10–100-fold lower affinity. Peptide linearization caused loss of affinity for all integrins and loss of specificity, whereas α-amino group acetylation increased the affinity for all tested integrins, but caused loss of specificity. These results highlight the critical role of molecular scaffold on the biological properties of NGR/isoDGR peptides. These findings may have important implications for the design and development of anticancer drugs or tumor neovasculature-imaging compounds, and for the potential function of different NGR/isoDGR sites in natural proteins.